'… they had interpreted "disability" as referring to a patently visible disability': experience of a patient group with NICE. Issue 7 (9th August 2022) - Barman-Aksözen, Jasmin; Granata, Francesca; Aksözen, Mehmet Hakan; Dechant, Cornelia; Falchetto, Rocco
Abstract: Erythropoietic protoporphyria (EPP) is an ultra-rare genetic disorder characterised by intolerance to visible light. Starting in early childhood, people with EPP suffer from social isolation, impaired educational and occupational opportunities, and low quality of life. Afamelanotide is the only effective and approved therapy for EPP. In England, its cost-effectiveness is currently assessed by the National Institute for Health and Care Excellence (NICE), which in 2018 issued a negative recommendation for funding. Stakeholder organisations, including our patient organisation, submitted appeals against the recommendation, which were upheld in all possible grounds. Moreover, the appeal panel expressed concerns about whether the evaluating committee discriminated against people with EPP and suggested that it seek guidance regarding the Equality Act 2010. However, three years later, the identified issues have not been addressed and patients in England remain without treatment. Afamelanotide represents another example for the trend towards a loss of fairness in NICE decisions.